2016
DOI: 10.3389/fcell.2015.00082
|View full text |Cite
|
Sign up to set email alerts
|

The RanGTP Pathway: From Nucleo-Cytoplasmic Transport to Spindle Assembly and Beyond

Abstract: The small GTPase Ran regulates the interaction of transport receptors with a number of cellular cargo proteins. The high affinity binding of the GTP-bound form of Ran to import receptors promotes cargo release, whereas its binding to export receptors stabilizes their interaction with the cargo. This basic mechanism linked to the asymmetric distribution of the two nucleotide-bound forms of Ran between the nucleus and the cytoplasm generates a switch like mechanism controlling nucleo-cytoplasmic transport. Since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(137 citation statements)
references
References 149 publications
4
127
0
Order By: Relevance
“…X. tropicalis spindles were also observed to possess distinct morphological features, including more robust kinetochore fibers and a more circular shape (Grenfell et al, ; Loughlin et al, ). Furthermore, whereas spindle assembly in X. laevis extracts required a chromatin‐generated gradient of RanGTP (Cavazza & Vernos, ; Kalab, Weis, & Heald, ), X. tropicalis spindle assembly was not affected by disruption of this pathway (Helmke & Heald, ). Therefore, not only spindle size, but also spindle architecture, morphology, and assembly mechanisms differ between these two species.…”
Section: Introductionmentioning
confidence: 99%
“…X. tropicalis spindles were also observed to possess distinct morphological features, including more robust kinetochore fibers and a more circular shape (Grenfell et al, ; Loughlin et al, ). Furthermore, whereas spindle assembly in X. laevis extracts required a chromatin‐generated gradient of RanGTP (Cavazza & Vernos, ; Kalab, Weis, & Heald, ), X. tropicalis spindle assembly was not affected by disruption of this pathway (Helmke & Heald, ). Therefore, not only spindle size, but also spindle architecture, morphology, and assembly mechanisms differ between these two species.…”
Section: Introductionmentioning
confidence: 99%
“…We found RAN (ras‐related nuclear protein) as a direct target for miR‐197‐3p using TargetScan which was validated further by performing qRT‐PCR and dual luciferase reporter assay. RAN is a small GTPase of the RAS superfamily and is involved in several biological processes, such as nucleocytoplasmic transport, nuclear envelope formation, and mitotic spindle assembly . Moreover, overexpression of RAN has already been reported in myriad of cancers, which is also correlated with poor prognosis, increased aggressiveness, and metastasis, inhibition of which can lead to suppression of cancer .…”
Section: Resultsmentioning
confidence: 99%
“…RAN is a small GTPase of the RAS superfamily and is involved in several biological processes, such as nucleocytoplasmic transport, nuclear envelope formation, and mitotic spindle assembly. [33][34][35] Moreover, overexpression of RAN has already been reported in myriad of cancers, which is also correlated with poor prognosis, increased aggressiveness, and metastasis, [36][37][38] inhibition of which can lead to suppression of cancer. 39 Therefore, to precisely address the oncogenic role of RAN in tumorigenesis of fibrosarcoma, which we found to be upregulated in fibrosarcoma as well.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to force generation within the spindle, dynein is also essential for 61 focusing microtubule minus--ends into the spindle poles (Echeverri et al,62 RanGTP regulated proteins have been identified and shown to play essential 77 roles in spindle assembly (Cavazza and Vernos, 2015). Recently we used a 78 mass spectrometry based proteomic approach to identify the full proteome 79 associated with RanGTP induced microtubules in Xenopus egg extracts and 80 validated a few selected proteins with no reported function in mitosis (Rosas--81 Salvans et al, 2018).…”
Section: Summary 29mentioning
confidence: 99%